2021
DOI: 10.1101/2021.11.01.21265700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and Validation of an Interpretable 3-day Intensive Care Unit Readmission Prediction Model Using Explainable Boosting Machines

Abstract: Intensive care unit readmissions are associated with mortality and bad outcomes. Machine learning could help to identify patients at risk to improve discharge decisions. However, many models are black boxes, so that dangerous properties might remain unnoticed. In this study, an inherently interpretable model for 3-day ICU readmission prediction was developed. We used a retrospective cohort of 15,589 ICU stays and 169 variables collected between 2006 and 2019. A team of doctors inspected the model, checked the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…We provided the TRIPOD (Transparent Reporting of a Multivariable Prediction Model for Individual Prognosis or Diagnosis) checklist ( 28 ) in Supplementary material 1 . This work was preregistered online ( 29 ); however, it had two deviations: a readmission interval of 3 days instead of 7 days was considered to exclude fewer patients with insufficient follow-ups. Also, we only performed external validation for the final performance results, which we considered most relevant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We provided the TRIPOD (Transparent Reporting of a Multivariable Prediction Model for Individual Prognosis or Diagnosis) checklist ( 28 ) in Supplementary material 1 . This work was preregistered online ( 29 ); however, it had two deviations: a readmission interval of 3 days instead of 7 days was considered to exclude fewer patients with insufficient follow-ups. Also, we only performed external validation for the final performance results, which we considered most relevant.…”
Section: Methodsmentioning
confidence: 99%
“…An overview of all steps conducted for this study can be found in Figure 1 . All code for preprocessing the data, training the models, and inspecting the final EBM model is publicly available ( 30 , 31 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cox R, Kaplan-Meier [13] SEER 2004-2016, # of variables is not disclosed, classification + regression for 3 categories: ≤6 months, 7-24 months, and ≥24 months ANN, RNN, CNN, RF, SVM, NB, GBM, LR [7] SEER 2010-2015, 12 variables, classification (1-, 3-, 5-year survival) XGB, LR, NB, DT, KNN, RF, SVM [14] SEER 2010-2015, 14 variables, classification (5-year survival) LR, NB, Gaussian K-base NB, [15] SEER 1973-2012, 114 variables, classification (0.5-, 1-, 5-year survival) RF, ANN Data Mining [16] SEER 2004-2009, 13 variables, classification + regression for 3 categories: ≤6 months, 7-24 months, and ≥24 months GBM, RF, GLM, EV Survival status prediction, length of survival estimation, and cancer patient clustering are primary topics found in the machine learning literature that utilizes the SEER dataset, where focus is placed on model accuracy. Moreover, common classification, clustering, and regression models employed within the second group of research include artificial neural networks (ANNs), support vector machines (SVMs), Naïve Bayes (NB), decision trees (DTs), random forest (RF), ensemble methods, K-means, and bidirectional data partitioning (BDP) [7,[13][14][15][16][17][18][19][20][21][22]. Apart from the great strides made in lung cancer prediction research, several challenges still exist:…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies explore survival status classification [7,14,15,17,18,21,22] and survival length prediction [19] individually, a scheme that leverages both remains elusive [13,16]. • Data used in lung cancer survivability predictions suffer from the class imbalance problem, which produces algorithm bias in favor of the majority class.…”
mentioning
confidence: 99%